La tolerancia en el contexto del interculturalismo - José Antonio Santos Arnaiz (Universidad Hemisferios, 2019)
From the perspective of interculturalism, this paper analyzes the importance of the authentic tolerance as a necessary element for a better integration of minorities in the context of postliberal states. Tolerance is understood as an unavoidable requirement for an authentic development of an open society, linked to a concept of freedom that advocates an understanding on an equal footing between different cultures including minority ones. The methodology consists in developing the concept of tolerance in relation to minorities using multidisciplinary references. The article has been divided into four sections: In the first section, it analyzes the context of tolerance from the perspective of interculturalism. The second section explains the authentic tolerance as an element for the integration of minorities in open societies. The third section tries to offer answers to the tolerance-freedom pairing. Finally, the fourth section draws some conclusions.